615.TOTAL PRODUCTIVE MAINTENANCE – TOOL TO IMPROVE THE COMPANIES PERFORMANCE - Andon, Naskovski; Gligorce, Vrtanoski (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
The research of the paper shows the implementation of TPМ methodology on total maintenance and its main tool, Autonomous Maintenance (AM). The goal is to increase the productivity and efficiency of an existing production line for pickling metal sheet. Total analysis of the production line is done by identifying weak points, i.e. assemblies using the Overall Equipment Effectiveness (OЕE) indicator. With applying the main tool, autonomous maintenance from TPM methodology, an attempt has been made to identify the anomalies, a system for reporting errors has been created, the number of standards and education of the operators has increased, and in order to reduce the number of delays in the production line. This will improve the efficiency of the employees and the productivity of the company as a whole.